Solid-fluid interfacial area measurement for wettability quantification in multiphase flow through porous media. (15th February 2021) - Singh, Deepshikha; Roy, Shantanu; Pant, Harish Jagat; Phirani, Jyoti
Highlights: Experiment protocol to determine solid-liquid interfacial area during multiphase flow devised. Dual-tracer method suitability for liquid-liquid flow in a fine porous medium determined. Dependence of the residual phase interfacial area with solid on wettability established. Abstract: Quantification of wettability inside a porous medium is challenging. Most of the currently available methods use either a proxy surface of the porous solid or a small sample of the porous medium for wettability quantification. Recognizing that more wetting fluid has more interfacial area with porous solid, we develop a tracer method to quantify the solid-liquid interfacial area for a porous medium. We use two tracers for a fluid-phase, an ideal tracer, and an adsorbing tracer. The ideal tracer follows the flow path, and the adsorbing tracer dynamically adsorbs on the porous surface. We use the tracers' mean residence time to quantify the solid-liquid interfacial area during multiphase flow in a porous medium. We conduct the tracer flow experiments at various saturations for a given wettability condition. We observe a monotonic behaviour of the wetted area with the fluid saturations. At the same residual saturation, oil has 10% less interfacial area with the porous solid in comparison to water. This difference in contact area can be used for quantifying the wettability using our methodology.